Photodissociation and photochemistry of V+(H2O)n, n = 1-4, in the 360-680 nm region - Scharfschwerdt, Björn; Linde, Christian van der; Balaj, O. Petru; Herber, Ina; Schütze, Doreen; Beyer, Martin K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The photodissociation and photochemistry of V+(H2O)n, n = 1–4, was studied in the 360–680 nm region in a Fourier transform ion cyclotron resonance mass spectrometer. The light of a high pressure mercury arc lamp was filtered with band pass filters, with center wavelengths from 360 to 680 nm in steps of 20 nm. The bandwidth of the filters, defined as full width at half maximum, was 10 nm. Photodissociation channels are loss of water molecules, as well as loss of atomic or molecular hydrogen, which may be accompanied by loss of water molecules. The most intense absorptions are red shifted with increasing hydration. Theoretical spectra are calculated with time dependent density functional theory. Calculations reproduce all features of the experimental spectra, including the red shift with increasing hydration shell and the overall pattern of strong and weak absorptions.